2009
DOI: 10.1007/s11239-009-0388-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and outcome in patients with retinal vein occlusion

Abstract: The pathogenesis and treatment of retinal vein occlusions (RVO) are largely unclear. Prevalence of cardiovascular risk factors and of thrombophilic abnormalities was evaluated in 117 patients (61 M, 56 F; mean age 51 +/- 13 years) with a history of RVO (62 central, CRVO; 48 branch, BRVO; 7 both) and in 202 age- and sex-matched control subjects. Cardiovascular outcome after a mean 8.2 year follow-up was recorded for 90 patients. Arterial hypertension was significantly more frequent in patients than in controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 37 publications
2
38
0
4
Order By: Relevance
“…A recent case-control study revealed the presence of antiphospholipid antibodies as a significant risk factor for developing RVO amongst 80 RVO patients aged 45 years or less, taking into account repeated antibody testing [55]. According to our findings, in a recent case-control study all ACA-positive patients were found amongst CRVO and not BRVO patients [42]. …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A recent case-control study revealed the presence of antiphospholipid antibodies as a significant risk factor for developing RVO amongst 80 RVO patients aged 45 years or less, taking into account repeated antibody testing [55]. According to our findings, in a recent case-control study all ACA-positive patients were found amongst CRVO and not BRVO patients [42]. …”
Section: Discussionsupporting
confidence: 66%
“…The authors acknowledged that this result was probably confounded by the small sample sizes, the lack of age adjustment and the type of patient cohorts found in the reviewed studies [13]. While some subsequent case-control studies more often found MTHFR homozygotes and/or high homocysteine levels amongst RVO cases compared to controls [40,41], others did not [12,42,43,44,45]. …”
Section: Discussionmentioning
confidence: 99%
“…The common cardiovascular predisposing systemic risk factors for RVO include hypertension, diabetes mellitus, and dyslipidemia [20,21,22,23,24]. According to a meta-analysis of 21 studies by O'Mahoney et al [24], hypertension and hyperlipidemia were most significantly associated with RVO; the odds ratios (ORs) were 3.5 [95% confidence interval (CI): 2.5-5.1; p < 0.05] and 2.5 (95% CI: 1.7-3.7; p < 0.05), respectively.…”
Section: Ocular and Systemic Risk Factorsmentioning
confidence: 99%
“…This major risk factor is more prevalent in patients with BRVO than in those with CRVO. More than 64% of RVO patients in the age group over 50 years are hypertensive, and it is a predominant finding in recurrent RVO (88%) [26,27]. Likewise, vascular events (cardiovascular, cerebral) are observed more often in patients with preexisting RVO [27].…”
Section: Risk Factorsmentioning
confidence: 99%